PEMILIHAN PEMASOK PADA MATERIAL KONSTRUKSI - Hasnaa Faadhilah; Agung Budi Broto (Universitas Widyatama, 2022)
Construction material considered very important in a construction project. Every activity that including materials is covers more than half of the total cost of the project and has a significant effect on the schedule. Against this background, the right supplier selection is needed. Supplier selection is a part of multi-criteria decision making where some criteria are considered to make the decision. This study was conducted to establish the criteria for selecting the best construction material supplier for highway project. The first step is criteria setting, then using the ANP method to get the priorities of each criterion. From this study, the three highest priority criteria are product quality (0.120), integrity of company personnel (0.091), and delivery performance (0.083).